2013
DOI: 10.6000/1927-5951.2013.03.01.5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimutagenic Activities of Optimized Extruded Desi Chickpea (Cicer arietinum L) Flours

Abstract: The objective of this study was to evaluate the effect of optimized extrusion cooking process on antioxidant and antimutagenic properties of desi chickpea cultivars. Three desi chickpea cultivars (Brown-ICC3512, Red-ICC13124, Black-ICC3761) were studied. Extrusion was carried out in a single-screw extruder; the operation conditions were previously optimized to obtain maximum antioxidant activity in extruded chickpea flour: Extrusion temperature (ET) = 155°C, and screw speed (SS) = 240 rpm. The antioxidant acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Antioxidant activity (AoxA), total phenolic compounds (TPC), total flavonoids (TF) and condensed tannins (CT) Gumul et al (2010) andFélix-Medina et al (2020) reported that the extrusion effect on AoxA depends on moisture content and processing temperature. The extrusion process induces the phytochemical release present in cellular walls, which are more available to quantify those (Garzón et al, 2013). Espinoza-Moreno et al (2016) reported an increase in antioxidant activity (AAox) and total phenolic compounds (TPC) in a whole amarantin transgenic maize: black common bean blend after the extrusion process.…”
Section: Proximate Composition and Nutritional Propertiesmentioning
confidence: 99%
“…Antioxidant activity (AoxA), total phenolic compounds (TPC), total flavonoids (TF) and condensed tannins (CT) Gumul et al (2010) andFélix-Medina et al (2020) reported that the extrusion effect on AoxA depends on moisture content and processing temperature. The extrusion process induces the phytochemical release present in cellular walls, which are more available to quantify those (Garzón et al, 2013). Espinoza-Moreno et al (2016) reported an increase in antioxidant activity (AAox) and total phenolic compounds (TPC) in a whole amarantin transgenic maize: black common bean blend after the extrusion process.…”
Section: Proximate Composition and Nutritional Propertiesmentioning
confidence: 99%